1031 Exploring the Impact of Cognitive Behavioral Therapy for Insomnia (CBT-I) on Daytime Productivity in Survivors of Breast Cancer. (27th May 2020) - Kieley, J; Walsh, N; McCarthy, J; Powell, E; Garland, S N
Abstract: Introduction: Post-treatment insomnia disorder and fatigue symptoms can impair work and daytime productivity in breast cancer survivors. Cognitive Behavioral Therapy for Insomnia (CBT-I) significantly improves insomnia and daytime fatigue. This feasibility study examined whether improving insomnia and fatigue using CBT-I is associated with improved work and activity productivity in breast cancer survivors. Methods: 10 survivors of early stage breast cancer participated in 7 weekly individual CBT-I sessions. The primary outcome was the Work Productivity and Activity Impairment Questionnaire-General Health (WPAIQ-GH) questionnaire. Secondary outcomes were the Insomnia Severity Index (ISI) and the Multidimensional Fatigue Symptom Inventory-Short Form (MFSI-SF). Assessments were conducted at baseline and post-treatment. Paired samples t-tests examined the impact of CBT-I on productivity and fatigue. Linear regression assessed whether change in fatigue was associated with change in productivity. Results: Participants had a mean age of 50.8 (range 42-63) and the majority were diagnosed with stage II (60%) cancer. There was a significant reduction in fatigue [t(9)= 2.43, p =.04] and activity impairment due to insomnia [t(9)= 3.105, p <.05] following treatment. Insomnia affected 52% of work productivity at baseline with a non-significant decrease to 15% following treatment [t(3)= 2.25 p= .110]. Reductions in fatigue were significantly associated with reductions in activity impairment [F(1, 8)= 7.25, p =.03], accounting for 47.5% of the variability. Conclusion: Treating insomnia with CBT-I significantly improved daytime productivity, activity impairment, and fatigue. Controlled research with larger sample sizes is warranted to confirm these preliminary results. Support: Nyissa Walsh is a trainee in the Cancer Research Training Program of the Beatrice Hunter Cancer Research Institute (BHCRI). Dr. Sheila Garland is supported by a Scotiabank New Investigator Award from BHCRI.